Variability of peak speed and sprinting actions during the same small-sided games: within- and between-player variations inspected over four consecutive weeks - Makar, Piotr; Silva, Ana; Kawczyński, Adam; Akyildiz, Zeki; Yildiz, Mehmet; Praça, Gibson; Clemente, Filipe (Biology of Sport, 2023)
This study aimed to analyze within- and between-player variations of peak speed and sprinting actions occurring in small-sided games (SSGs: 1v1 and 5v5). The study followed a cohort study design. Twenty male youth soccer players (age: 17 years old) from the same team were observed over four consecutive weeks. Each week, the players participated in two sessions (day one and day two) during which SSGs were applied. The 1 vs. 1 format was employed with four repetitions of thirty seconds interspaced with two-minute rest intervals, while the 5 vs. 5 format with four repetitions of four minutes and two-minute rest intervals between them. The players were monitored during all training sessions with the Polar Team Pro. The peak speed attained in each game, and the number of sprints were extracted as the primary outcomes. The between-player variability revealed a lower coefficient of variations for peak speed in the 1 vs. 1 (13.9%) and 5 vs. 5 (10.9%) formats than for sprints (1 v 1: 64.7%; 5 v 5: 65.5%). Considering the within-player variability, it was observed that sprints were more variable (1 vs. 1: 62.1%; 5 v 5: 65.7%) than peak speed (1 vs. 1: 16.4%; 5 v 5: 14.0%). The between-session analysis revealed that during week 1 (day 1), peak speed was significantly higher than during week 3 (day 1) in the 1 vs. 1 format (+3.0 km/h; p = 0.031; d = 1.296). Moreover, peak speed during week 3 (day 2) was considerably lower than during week 1 (–5.9 km/h; p 0.05). However, on day two, the sprint was substantially higher during week one than during week four in the 5 vs. 5 format (+5.40 n; p = 0.002; d = 2.571). In conclusion, this study revealed that peak speed presents lower within- and between-player variability than the number of sprints. Considering these two measures, there are no considerable variations between the weeks. Coaches should consider identifying strategies to stabilize the stimulus regarding the number of sprints if this represents one of the targets for employing SSGs.